Product Market Competition and Economic Performance in the United States - Suppanz, Hannes (OECD Publishing, 2004)
Regulatory reform efforts in a broad range of industries have resulted in increased importance of competitive forces as a means to allocate resources and improve economic efficiency. A number of indicators suggest that such forces have been stronger in the United States than in most other OECD countries for some time. This has contributed to sizeable productivity gains and good economic performance over the past decade or so. Nonetheless, despite the generally pro-competitive thrust of policies, a number of challenges remain. Although there are few sectors of the economy from which competition policy and law are completely excluded, given the high risk of sanctions and damages for violation, many anomalous exemptions and special regimes have found their way into US legislation. Contrary to other OECD countries, government related firms are exempted from competition enforcement. Intellectual property rights create special challenges for competition policy and some problems have followed their strengthening over the past two decades, such as the soaring cost of patent litigation. The generally favourable experience with deregulation created pressures for liberalisation in network industries, where the United States has rather been a laggard, at least in the electricity sector. Reforms in the 1990s have entailed some positive results but also some setbacks, reflecting both the difficulties in ensuring competition in such industries and policy mistakes
Keywords: Economics; United States